Oscillatory Dynamics and In Vivo Photoacoustic Imaging Performance of Plasmonic Nanoparticle‐Coated Microbubbles. Issue 25 (20th February 2015) - Dixon, Adam J.; Hu, Song; Klibanov, Alexander L.; Hossack, John A.
<x xml:space="preserve">Abstract</x> Microbubbles bearing plasmonic nanoparticles on their surface provide contrast enhancement for both photoacoustic and ultrasound imaging. In this work, the responses of microbubbles with surface‐bound gold nanorods—termed AuMBs—to nanosecond pulsed laser excitation are studied using high‐speed microscopy, photoacoustic imaging, and numerical modeling. In response to laser fluences below 5 mJ cm−2, AuMBs produce weak photoacoustic emissions and exhibit negligible microbubble wall motion. However, in reponse to fluences above 5 mJ cm−2, AuMBs undergo dramatically increased thermal expansion and emit nonlinear photoacoustic waves of over 10‐fold greater amplitude than would be expected from freely dispersed gold nanorods. Numerical modeling suggests that AuMB photoacoustic responses to low laser fluences result from conductive heat transfer from the surface‐bound nanorods to the microbubble gas core, whereas at higher fluences, explosive boiling may occur at the nanorod surface, producing vapor nanobubbles that contribute to rapid AuMB expansion. The results of this study indicate that AuMBs are capable of producing acoustic emissions of significantly higher amplitude than those produced by conventional sources of photoacoustic contrast. In vivo imaging performance of AuMBs in a murine kidney model suggests that AuMBs may be an effective alternative to existing contrast agents for noninvasive photoacoustic and ultrasound imaging applications.